Kesenjangan Literasi Digital antara Staf Gudang Senior dan Driver Muda dalam Menggunakan Sistem Barcode Mobile: Studi Fenomenologi terhadap Kesalahan Verifikasi - Sandopart, Dewa Putu Yohanes Agata L. (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to explore in depth the subjective experiences of the digital literacy gap between senior warehouse staff and young drivers in using mobile barcode systems and to analyze how this gap contributes to verification errors in warehouse environments. This study employs a qualitative approach with an interpretative phenomenological design. Twelve participants were selected through purposive sampling, consisting of six senior warehouse staff aged 47–55 years and six young drivers aged 22–28 years. Data were collected through semi-structured in-depth interviews, non-participant observation, and document review, and analyzed using a seven-stage phenomenological analysis framework. The study identifies five main themes, including technological disorientation among senior staff reflected in confusion with new interfaces and difficulty distinguishing visual feedback, disparities in digital processing speed that create psychological pressure, cross-generational communication barriers due to differences in terminology and age hierarchy, failure of informal knowledge transfer caused by training methods that do not align with senior workers’ characteristics, and maladaptive coping strategies such as responsibility reduction and the use of dual manual-digital systems. This study contributes by shifting the focus from quantitative measurement of error rates to a phenomenological understanding of how the digital literacy gap is experienced by both groups and by identifying a positive feedback loop that exacerbates the gap in warehouse environments.